2023
DOI: 10.4102/safp.v65i1.5702
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to insulin use in type 2 diabetes mellitus

Abstract: The benefits of the newer antidiabetic agents available for managing type 2 diabetes mellitus (T2DM) remain indisputable, but many patients will require insulin therapy in the disease course. Given the limited access to newer antidiabetic agents, insulin remains a standard treatment modality in T2DM in South Africa. Early, multifactorial intervention remains ideal, but glucose, blood pressure and cholesterol values remain above target in many countries. Barriers to achieving glucose control in South Africa inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Insulin therapy has been the main treatment option for patients with T2D for over a century and it is ultimately required in the chronic management of T2D, if glycaemic targets are not achieved following dietary intervention, review of physical activity behaviour, and oral anti-hyperglycaemic medication [5,11]. There is often a delay in commencing insulin therapy, due to hesitancy both among patients to take insulin and healthcare providers to prescribe [12]; a survey of 66,000 patients found that average HbA1c was 80 mmol/mol at the start of insulin therapy and over 90% of participants already had associated complications [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin therapy has been the main treatment option for patients with T2D for over a century and it is ultimately required in the chronic management of T2D, if glycaemic targets are not achieved following dietary intervention, review of physical activity behaviour, and oral anti-hyperglycaemic medication [5,11]. There is often a delay in commencing insulin therapy, due to hesitancy both among patients to take insulin and healthcare providers to prescribe [12]; a survey of 66,000 patients found that average HbA1c was 80 mmol/mol at the start of insulin therapy and over 90% of participants already had associated complications [13].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin is available in numerous formulations (e.g., rapid-acting, short-acting, intermediate-acting, long-acting) to enable the dose and timing to be matched to an individual's physiological requirements [11]. The global median government procurement price for a standardised 100 U/10 mL vial of human insulin is USD 5, compared to long-lasting 'analogue' insulin at USD 33; the individual pays USD 9 for human insulin at pharmacies and private hospitals [14].…”
Section: Introductionmentioning
confidence: 99%